PCOD and PCOS: Are they same or Different ??? - Rao, Bhagya Venkanna (Journal of Pharmacy Practice and Community Medicine)
Dear Readers, When we hear the terms "PCOD" and "PCOS," the first thing we probably think of is "irregular periods," isn't it? Regarding these diseases, there is still a lot of ignorance. The two abbreviations are frequently used interchangeably, despite the fact that they refer to two quite different conditions, and there is a lot of misinformation and myths surrounding these surprisingly common health problems.